Persepsi Mahasiswa Hubungan Internasional di Universitas Mulawarman Terhadap Body Positivity Pasca Kemenangan Abena Appiah di Miss Grand International Tahun 2020 - Farabi, Ibnu; Anggraini, Yayuk (Interdependence Journal of International Studies, 2023)
This study aims to determine the perceptions of International Relations Students at Mulawarman University towards Body Positivity following Abena Appiah's victory in Miss Grand International 2020, as well as the implications of Abena Appiah's victory for international relations and association between nations by using Identity Political Theory and Body Image Concepts. The type of data used is in the form of primary and secondary data through qualitative data analysis techniques. The results of the study show that the body positivity movement is accepted by International Relations Students at Mulawarman University as a positive renewal movement in respecting and accepting one's posture/body shape even though it is different from the posture/body shape of other people. The implications of Abena Appiah's victory on patterns of international relations and association between nations are positive. On the one hand, it is a strong signal and a reminder alarm for all countries/nations how the concept of beauty does not recognize and is not imprisoned by state administrative boundaries or primordial boundaries such as ethnicity, nation, race, skin color, certain religions.